SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SEKOLAH HARAPAN LESTARI - Timothius Simon; Dali Santun Naga; Wasino Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Library management at Harapan Lestari School, such as borrowing books and book data, is still in a manual process, so there are often difficulties in making reports and in storing existing data. These problems make Sekolah Harapan Lestari have the desire to have an Information System in their library, which can overcome existing problems. Therefore a web-based library information system was designed by using PHP, MySql, and XAMPP with the System Development Life Cycle (SDLC) method in the hope of helping in the process of managing libraries in Harapan Lestari School.The function of the program, among others: from the Front End are the registration to become a member of the library, view the book catalog, make loans see the list of loans along with their status, see a list of returns, see a list of fines and their status, see a list of lost or damaged books and their status. From the Back End side, it can manage books, confirm various kinds of events in the library such as borrowing repayments, fines, replacing lost or damaged books, and reports